Making equal rights to health an election issue in NZ local body elections. (30th September 2020) - Stone, P; Leyland, D e b
Abstract: In New Zealand there are 20 district health boards (DHBs) with local elections every 3 years. There is low voter turnout for these, we suspect because the public has low cognizance of the role DHBs have in governing their health and disability system. Good governance ensures everyone whatever ethnicity, gender or sexual proclivity, from birth to old age, able or disabled, mentally well or unwell, drugfree or addicted, has equal rights of dignified access to healthcare. Without public engagement in DHB elections, the community risks having candidates elected that also don't understand their role through a preventative public health framework or human rights lens. The United Community Action Network (UCAN) developed a human rights framework and Health Charter for people driven into poverty by the costs of staying well in NZ. The framework outlines 6 social determinants of health needing protection through policy, to ensure all enjoy their rights to health. UCAN and the Public Health Association of New Zealand (PHA) partnered to raise public and the candidates' awareness during 2019 elections, of these social determinants causing inequity in health outcomes. A series of short explainer-videos were created for sharing through social media during the election build-up period, helping to promote PHA Branches' public Meet the Candidates events. Post-election, a longer film was produced to send to the elected DHB members. Our theory of change centred on spotlighting health inequity for voters, so that they would elect DHB members who had the greatest understanding and commitment to addressing this issue. With shareable videos we aimed to attract audience, raise awareness and debate the policy solutions to health inequity with candidates, enabling more informed choice amongst the voting public. Post-election, we maintain supportive relationships with the elected DHB members that promised their commitment to our Health Charter during their campaigns. Key messages: Using videos and social media, local body elections provide an opportunity to promote everyone's right to affordable healthcare, supporting and informing voter decision-making. UCAN's Health Charter is an advocacy resource for raising awareness of the social determinants of health inequity and poverty for people with mental illness, addiction and disability.